Phonon-assisted NIR-to-visible upconversion in single β-NaYF4 microcrystals codoped with Er3+ and Yb3+ for microthermometry applications: Experiment and theory - Gonçalves, I. M.; Pessoa, A. R.; Hazra, C. [UNESP]; Correales, Y. S. [UNESP]; Ribeiro, S. J.L. [UNESP]; de, L. (Elsevier, 2021)
Owing to the tremendous possibility of contactless temperature probing with micro- and nanometric spatial resolution, photoluminescent single-particle thermometry at the micro or nanoscale is rapidly advancing towards its successful applications in electronics, biological thermal imaging, or investigating thermodynamics around microsystems, for instance. The first step is the characterization of a suitable sized particle which will play the role of a thermometer in the desired/needed size scale. To that end, possibilities of using Er3+/Yb3+ doped β-NaYF4 rare-earth single microcrystals are explored particularly in this work due to its luminescence efficiency in the visible band and morphological stability in a temperature range compatible with biological systems. Under CW excitation at 977 nm, the Er3+ ions in β-NaYF4 host allow observing photoluminescence around 525 nm and 547 nm, corresponding to the 2H11/2 → 4I15/2 and 4S3/2 → 4I15/2 transitions, respectively. As these 2H11/2 and 4S3/2 states are close enough in energy, it is expected the Luminescence Intensity Ratio (LIR) to follow a Maxwell-Boltzmann thermal distribution, but experiments performed in this work present a deviation from this prediction. This discrepancy is explained by an analytical and numerical solution of a system of rate equations, which shows that the nonradiative decay from 4S3/2 to 4F9/2 and the mechanism of excitation of the thermally coupled levels play an important role in the LIR analysis.
Keywords: Lanthanide codoped systems; Luminescent materials spectroscopy; Single upconversion micro-crystals; Single-particle thermometry